Virtual Compensatory Cognitive Training (Virtual-CCT) – A study on acceptability and feasibility - Subhashini Gopal; Lakshmi Venkatraman; B Suhavana; Pooja Sivaji; Frances Dark; Padmavati Ramachandran (Industrial Psychiatry Journal)
Background: Cognitive impairments in individuals with psychotic disorders impact day-to-day activities and social and occupational functioning (Bowie CR, 2006). Most of the cognitive interventions were developed in the west focusing mainly on clinical research and were not available in routine care. Adaptability and accessibility of these techniques in low-resource settings like India had major challenges. Keeping this in mind, Compensatory Cognitive Training (CCT), being an economical and noncomputerized intervention, was adapted to be used for an urban English-speaking population in India. Aim: The study aimed to determine the acceptability and feasibility of delivering CCT to persons with schizophrenia through virtual one-on-one sessions. Materials and Methods: Patients with a diagnosis of schizophrenia were assessed for their subjective and objective cognitive deficits. CCT was delivered for 13 participants as a virtual one – one session. Three participants dropped out midway. Semistructured interview was conducted with all ten participants who completed the intervention to understand their acceptability of Virtual CCT. Feasibility was assessed using a visual analog scale on their attendance, involvement, and comprehending ability. The mean percentile scores on cognitive domains at baseline and end of intervention were analyzed. Results: Significant change was observed in specific domains of cognition. Participant involvement, lesser dropout rates, and their feedback indicated that Virtual CCT is a feasible and acceptable intervention. Conclusion: Virtually delivered CCT appears to be an acceptable and feasible intervention to increase access to cognitive interventions for persons with schizophrenia in LAMI countries. This needs to be tested in larger populations.